Workplace comfort: a necessity for employee health and well-being - Jamlus, Suhaida; Abu Bakar, Norjannah; Abdul Wahid, Nor Hashimah (Faculty of Accountancy, 2025)
A conducive workplace plays a vital role in promoting employees' health and supporting a healthy lifestyle. This conducive workplace environment, which includes factors such as comfortable physical settings, supportive management, and positive workplace culture, is an important element in ensuring organizational effectiveness and employee well-being. A study conducted by Kamarulzaman et al. (2011) shows that organizations need to manage human resources not only in terms of salary or benefits, but also through a conducive work environment at supports the emotional, mental and physical growth of their employees. Aspects of the work environment that affect performance and employee well-being include workplace design, indoor climate, noise and positive workplace culture (Kamarulzaman et al., 2011 ).